Study on flexural behavior of coral concrete beams reinforced with CFRP bars. (May 2022) - Deng, Zhiheng; Zhong, Xiangjun; Liu, Bing; Wen, Kun
Abstract: The rational use of coral aggregate in concrete production is of great significance to reduce the cost and period of island construction. However, using steel rebars in coral concrete structure is impractical given the corrodibility of steel in marine environment. To this end, this study experimented the use of carbon fiber reinforced polymer (CFRP) bars as a replacement for regular reinforcement, and 12 coral concrete beams reinforced with CFRP bars (CCBRC) specimens were experimentally researched. The failure mode, concrete strain, CFRP bar strain, mid-span deflection, maximum crack width and ultimate flexural capacity were studied, and an applicable design equation for this type of members was established based on the results. The results showed that the crack width reaching 1.5 mm is the main failure mode. The concrete strain of mid-span section conforms to the plane section assumption, and the load-CFRP bars strain curve is bilinear. In addition, the load level of beam specimen is low when it reaches the limit value of deflection and crack width in normal service, and the established formula can reliably predict the ultimate flexural capacity.